Predecibilidad del tráfico en redes modernas de comunicaciones - Alzate Monroy, Marco Aurelio; Vega Stavro, José Felix (Ingeniería, 2001)
This paper presents the results of some experiments that allow determining the predictability in a real traffic trace with fractal behavior. The conclusion is that without fitting the trace to any particular self-similar model, is possible to use typical point statistical to predict, with high grade of precision, the traffic intensity in the near future. Finally we discuss about the use of this results for congestion control in modern telecommunications networks. The paper explains, in a tutorial manner, both the theory and the experiments. The final section presents some investigation results about congestion control protocols based on predictability, obtained with the discrete event simulator NS-2.